Double bass blues - Loney, Andrea J. (Alfred A. Knopf, 2019)
After school orchestra practice, young Nic carries his double bass through rough neighborhoods to his grandfather's home, where he and Grandaddy Nic play jazz music with friends, delighting the neighbors.